2018
DOI: 10.1088/1755-1315/170/2/022036
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Dialkyldithiophosphate as self-sulfurized catalyst precursor in Hydrocracking of Residue

Abstract: Abstract. The molybdenum dialkyldithiophosphate (MoDTP) with the feature of selfsulfurization, has been prepared, characterized and evaluated in the slurry-phase hydrocracking of Karamay atmospheric residue (KAR) as catalyst precursor. The selfsulfurization of MoDTP achieved fine MoS 2 particles with lower crystallinity and higher surface Mo 4+ proportion in contrast to that of molybdenum naphthenate, implying the well sulfurized statement of MoDTP. Low coke yield and large asphaltene aggregate size using MoDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…However, there has been a growing interest in other, less conventional, methods of improving HDC as a process [17]. An overview of recent HDC studies can be found in Table S1 [18][19][20][21][22][23][24]. Additional reviews on HDC of heavy oils can be found elsewhere [17,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been a growing interest in other, less conventional, methods of improving HDC as a process [17]. An overview of recent HDC studies can be found in Table S1 [18][19][20][21][22][23][24]. Additional reviews on HDC of heavy oils can be found elsewhere [17,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%